Management of infectious waste from COVID-19 self-isolation patient in Puskesmas Kasihan 2 working area - Khairani, Nadhira; Rahastri, Ajeng; Surbakti, Hana Yesica (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to explore the management of infectious waste in COVID-19 self-isolated patients in ​Ngestiharjo and Tirtonirmolo villages of Puskesmas Kasihan 2, Kasihan Bantul Regency. Method: The study used a qualitative research design. Stakeholders and technical officers related to waste management in the study area were selected to be informants. Data were collected during September – October 2021 by in-depth interview and analyzed using thematic analysis techniques. Data source triangulation was conducted to improve the trustworthiness of the data. Results: This analysis showed two themes related to the management of infectious waste generated by self-isolation patients. The first one is the incompatibility of waste handling implementation. The patients should be responsible for the infectious waste they generate so that burning waste and mixing it with general household garbage becomes an issue. The other theme Is the importance of local policy regarding the COVID-19 waste management. Since the pandemic, waste management has been referring to the Ministry of Environment and Forestry policy (SE.3/MENLHK/PSLB3/PLB.3/3/2021), which was not socialized to the local community so that infectious waste did not become a concern of Covid-19 control in the area. Conclusion: A policy directly related to infectious waste from self-isolated patients is essential in implementing safe infectious waste management. Besides, the lack of adequate facilities and human resources also contributed to the issues.